2021
DOI: 10.1002/ajim.23244
|View full text |Cite
|
Sign up to set email alerts
|

COPD risk among older construction workers—Updated analyses 2020

Abstract: Background A 2010 study of construction workers participating in medical screening programs at the Department of Energy (DOE) nuclear facilities demonstrated increased chronic obstructive pulmonary disease (COPD) risk. The current study of a larger worker cohort allowed for a more nuanced analysis of COPD risk, including for employment beginning after the mid‐1990s. Methods Study participants included 17,941 workers with demographic and smoking data and spirometry with a minimum of three recorded expiratory ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 64 publications
(121 reference statements)
2
12
0
Order By: Relevance
“…Many studies showed that occupational exposure is characterised by regular exposure to fumes, inorganic and organic fine dust, and many chemicals [ 18 , 19 , 20 ]. The industry, construction, and agriculture workers are the main occupations, associated with the risk of CRD [ 21 , 22 , 23 ]. In the present study, the most commonly exposed occupation among the patients were industry workers (22.1%), construction workers (10.6%), and drivers of vehicles using petrol (13.2%).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies showed that occupational exposure is characterised by regular exposure to fumes, inorganic and organic fine dust, and many chemicals [ 18 , 19 , 20 ]. The industry, construction, and agriculture workers are the main occupations, associated with the risk of CRD [ 21 , 22 , 23 ]. In the present study, the most commonly exposed occupation among the patients were industry workers (22.1%), construction workers (10.6%), and drivers of vehicles using petrol (13.2%).…”
Section: Discussionmentioning
confidence: 99%
“…Analyses focused on respiratory diseases (COPD and pneumoconiosis), lung cancer mortality, and hearing impairment, including risk of these outcomes by time period since first entry into construction work. Previous studies of the BTMed population have shown that construction trades workers are at significantly increased risk for all these adverse health conditions 3–6,40 …”
Section: Methodsmentioning
confidence: 99%
“…In clinical practice, COPD is diagnosed based on a combination of symptoms and pulmonary function, often including post‐bronchodilator spirometry. However, most prior epidemiologic studies of worker populations, including the BTMed cohort, have used an epidemiologic case definition for COPD based on spirometry without bronchodilation, and we have adopted this definition for the current study 2,5,42,43 . The ATS/ERS Task Force 44 recommends identification of airway obstruction based on an FEV 1 /FVC ratio below the lower limit of normal (LLN) to avoid age‐related misclassification associated with use of a fixed FEV 1 /FVC ratio 45–48 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations